Teaching India And China In A World History Curriculum - Sethia, Tara (Teaching History: A Journal of Methods, 1996)
India and China represent two of the core Asian traditions as well as two of the oldest strands in the fabric of world civilizations. Indian and Chinese religions, philosophies, art, literature, technologies, and social systems have played a fundamental role in defining the human heritage and thus merit a careful assessment of their role in the world history curriculum.